EFFECT OF LONG TERM FERTILIZATION ON GRAIN YIELD AND YIELD COMPONENTS OF WINTER TRITICALE - D. Terzic; V. Djekic; S. Jevtic; V. Popovic; A. Jevtic; J. Mijajlovic; A. Jevtic (Journal of Animal and Plant Sciences, 2018)
Investigation about effect of high amounts of nitrogen and source of nutrition on winter triticale productivity was carried out in a stationary field trial in the Sumadija region, in Central Serbia. This study was conducted over a period of three years ( 2009-2011) on a vertisol soil to evaluate the effect of different fertilization methods on grain yield and yield components of winter triticale variety. Treatments included control and six fertilization variants with different combinations of NPK fertilizers (N, NK, NP , NP , NP K, and NP K). Investigation showed a considerable variation of 1 2 1 2 grain yield depending on mineral nutrition. The highest and statistically significant average grain yields were achieved -1 -1 -1 under NP K ( 4.105 t ha ) and NP K (4.050 t ha ) treatments. The combined use of NP K fertilizers (120 kg N ha , 60 1 2 1 -1 -1 -1 -1 -1 kg P O ha , 60 kg K O ha ) and NP K treatment (120 kg N ha , 100 kg P O ha , 60 kg K O ha ) represented the 2 5 2 2 2 5 2 excellent base for optimum stock of major nutrients, resulting in maximum grain yield. Thousand grain weight of triticale significantly varied across years, the highest average 1000-grain weight of winter triticale investigated was achieved in the NP K variant ( 44.81 g). Grain yield was significantly positively correlated with 1000-grain weight only 1 in all years. potential in the different environment of growing
Keywords: fertilization; yield; quality; triticale